A comparative study between learning by memorization and learning by reading score among bass guitar players / Muhammad Fikri Hozain and Mohammad Fazreen Ikhmal Nordin. - Hozain, Muhammad Fikri; Nordin, Mohammad Fazreen Ikhmal (2020)
The purpose of this study is to increase the understanding on the importance between two types of learning method that usually used by bass guitar player while practicing the songs. The methods are learning by reading score and learning by memorization. This study also will observe the most preferred method and also the effectiveness. For this study, music students majoring in electric bass guitar and bass guitar players will be the subjects. The sample that I choose for this study is limited to three music students majoring in electric bass guitar and three bass guitar players who had experienced performing or teaching more than 1 year. This is to ensure that the data obtained is relevant and the findings could answer the research questions above.